2001
DOI: 10.1108/02634500110363772
|View full text |Cite
|
Sign up to set email alerts
|

Salespeople characteristics, sales managers’ activities and territory design as antecedents of sales organization performance

Abstract: The impact of characteristics of salespeople, activities of sales managers and territory design are investigated as antecedents of sales organization performance among Canadian salesforces. Based on MANOVA analysis of responses from 102 field sales managers, more effective sales organizations have salespeople who are more motivated, employ managers who direct more and are more satisfied with the design of their territories. Sales managers must adopt better people and communication skills to train and direct th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Sales managers play a critical role in establishing and maintaining salesperson and customer relationships by enforcing management policies designed to guide and shape salesperson behavior. These policies – monitoring, directing, evaluating and rewarding salespeople – influence their go-to-market strategies, customer selection as well as motivation and direct selling effort (Tansu Barker, 2001; Høgevold et al , 2022). Research recommends no single best sales management policy, so managers should implement behavioral and outcome controls that best align firm and salesforce needs (Anderson and Oliver, 1987).…”
Section: A Multi-stakeholder Multi-outcome Perspective Of the Sales F...mentioning
confidence: 99%
“…Sales managers play a critical role in establishing and maintaining salesperson and customer relationships by enforcing management policies designed to guide and shape salesperson behavior. These policies – monitoring, directing, evaluating and rewarding salespeople – influence their go-to-market strategies, customer selection as well as motivation and direct selling effort (Tansu Barker, 2001; Høgevold et al , 2022). Research recommends no single best sales management policy, so managers should implement behavioral and outcome controls that best align firm and salesforce needs (Anderson and Oliver, 1987).…”
Section: A Multi-stakeholder Multi-outcome Perspective Of the Sales F...mentioning
confidence: 99%
“…Piercy et al (2004b) stated the positive impact of the outcome control system on the effectiveness of the sales organization. Another study by Barker (2001) concluded that more effective organizations have a higher salary ratio and that the managers are very active in directing and training the sales force. This implies that organizations which use behaviour-based control are more effective.…”
Section: Salesforce Characteristicsmentioning
confidence: 99%